Identification Analysis of Eukaryotic Expression Plasmid Rap2a and Its Effect on the Migration of Lung Cancer Cells - Jinxia WU; Miaomiao SANG; Wenjia CAO; Junnian ZHENG; Dongsheng PEI (Chinese Journal of Lung Cancer, 2014)
Background and objective Rap2a, a member of the small GTPase superfamily, plays a critical role in regulating the function of integrin and cell adhesion, thereby controlling cell motility and cell/matrix interactions. However, the function of Rap2a in carcinogenesis is still poorly understood. To clone Rap2a cDNA, which belongs to human Ras-related small G protein superfamily, we constructed its eukaryotic expression vector and determined its expression in lung cancer cells. The aim of this study is to explore the role of Rap2a in carcinogenesis. Methods The levels of endogenous Rap2a protein in lung cancer cells were measured by Western blot. Total RNA of human osteosarcoma cells U2OS was extracted and reverse-transcribed into cDNA by RT-PCR. Then, Rap2a gene was amplified by PCR and inserted into pcDNA3.1(+). The reconstructed plasmid was identified by restricted enzyme digestion and sequencing. pcDNA3.1(+)-Rap2a was transfected into H1299 and A549 cells, the expression of Rap2a was detected by Western blot. In addition, the migratory abilities of lung cancer cells were evaluated by Transwell assay. Matrix metalloproteinase (MMP)2 enzyme activity was evaluated by gelatin zymography. Results Rap2a is significantly upregulated in lung cancer cells. The results of enzyme digestion and sequencing showed that the coding sequence of pcDNA3.1(+)-Rap2a was right and was inserted into the vector correctly. The results of Western blot showed that H1299 and A549 cells were transfected successfully. Transwell assay indicated that the ectopic expression of Rap2a promotes lung cancer cells migration. Correspondly, enzyme activity of MMP2 also increased. Conclusion Eukaryotic expression plasmid pcDNA3.1(+)-Rap2a was constructed successfully. Rap2a could be expressed in lung cancer cells efficiently and promotes lung cancer cell migration.